The relationship between performance of a single-leg squat and leap landing task: moving towards a netball-specific anterior cruciate ligament (ACL) injury risk screening method. Issue 4 (3rd July 2020) - Fox, Aaron S.; Bonacci, Jason; Saunders, Natalie
ABSTRACT: Field-based screening methods have a limited capacity to identify high-risk postures during netball-specific landings associated with anterior cruciate ligament (ACL) injuries. This study determined the biomechanical relationship between a single-leg squat and netball-specific leap landing, to examine the utility of including a single-leg squat within netball-specific ACL injury risk screening. Thirty-two female netballers performed single-leg squat and netball-specific leap landing tasks, during which three-dimensional (3D) kinematic/kinetic data were collected. One-dimensional statistical parametric mapping examined relationships between kinematics from the single-leg squat, and the 3D joint rotation and moment data from leap landings. Participants displaying reduced hip external rotation, reduced knee flexion, and greater knee abduction and knee internal rotation angles during the single-leg squat exhibited these same biomechanical characteristics during the leap landing ( p < 0.001). Greater ankle dorsiflexion during the single-leg squat was associated with greater knee flexion during landing ( p < 0.001). Ankle eversion during the single-leg squat was associated with frontal and transverse plane knee biomechanics during landing ( p < 0.001). Biomechanics from the single-leg squat were associated with landing strategies linked to ACL loading or injury risk, and thus may be a useful movement screen for identifying netball players who exhibit biomechanical deficits during landing.